Regional hub port development: The case of Montevideo, Uruguay - Gordon Wilmsmeier; Inmaculada Martínez-Zarzoso; Norbert Fiess (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2010)
This paper reflects on port development in Uruguay in an environment of trilateral interport competition. The regional characteristics of port development in terms of their geographical, functional and operational characteristics are discussed by analysing the port system's evolution. The case of Montevideo as the success or failure of a regional hub port development strategy is analysed in detail. Particular attention is given to the evolution and impact of the liner shipping service network in defining the role of a port within a regional port system. Further, the evolution of the port of Montevideo in terms of institutional and organisational and the related strategy are described, with focus on the effect on transhipment cargo in the port. The main findings are twofold. First, port development in Montevideo been driven proactively and under a clear strategy, but still faces a number of challenges. Second, economies of scale in transport, port infrastructure and connectivity are important determinants of port development, of which the latter is principally driven by external actors, the shipping lines. The paper shows that despite strong efforts Uruguay and its principal port Montevideo are highly dependent on external factors, particularly the level of connectivity, in their strategy to develop Montevideo as a regional hub. Thus the findings are relevant in relation to the discussion of Montevideo's development potentials as a hub on South America's East Coast in particular and the effects of external influences on port development from in general.
Keywords: 330; regional port development; transhipment; connectivity; distance; Latin America; Hafenentwicklung; Hub-and-Spoke System; Internationaler Wettbewerb; Montevideo